Asynchronous Speeds: Disentangling the Discourse of 'High-Speed Broadband' in Relation to Australia's National Broadband Network. Issue 1 (May 2014) - Dias, Marcos P.; Arnold, Michael; Gibbs, Martin; Nansen, Bjorn; Wilken, Rowan
This article analyses the substantive problems related to the term 'high-speed broadband' in relation to the implementation of Australia's National Broadband Network (NBN). It argues that an understanding of speed in relation to broadband must take into account a complex assemblage of infrastructure networks, communication devices, software, location, user subjectivity and political input. Within this assemblage are varied definitions, discourses and materialities of speed that do not necessarily synchronise. Instead, speed is subject to asynchronous perceptions and implementations, which impact on the potential of the NBN. With the aim of contextualising and problematising the understanding of speed in relation to the NBN, this article explores four key points: first, how the perception of speed is dependent not so much on technical performance, but on the subjectivities of internet experience; second, how the term 'broadband' is politically shaped, especially in the context of the Coalition government's alternative multi-technology mix plan; third, how the assemblage of different social, technical and political actants that constitute high-speed broadband determines the perception of speed; and finally, how asynchronous speeds of broadband implementation and adoption may impact on the potential benefits of the NBN.